1978
DOI: 10.1084/jem.148.2.592
|View full text |Cite
|
Sign up to set email alerts
|

Ir-genes in H-2 regulate generation of anti-viral cytotoxic T cells. Mapping to K or D and dominance of unresponsiveness.

Abstract: H-2 dependent and virus-specific Ir genes regulate the generation of primary virus-specific K or D restricted cytotoxic T-cell responses in vivo. The following examples have been analyzed in some detail: first, Dk restricted responses to vaccinia in Sendai viruses are at least 30 times lower than the corresponding K-restricted responses irrespective of the H-2 haplotypes (k, b, d, dxs, dxq) of K and I regions; in contrast, LCMV infection generates high responses to Dk. These findings are consistent with but do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
67
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(77 citation statements)
references
References 25 publications
(35 reference statements)
10
67
0
Order By: Relevance
“…We have shown that preference of H-Y-specific CTL for H-2 k occurs also in B6 --~ B6 X CBA chimeras, i.e., that the radioresistant tissue of the chimeric hosts influences the preference of H-Y-specific CTL for certain H-2 alleles (14). Similar observations on allele preference of virus-specific CTL have been made by Zinkernagel et al (15,16), Doherty et al (17), and Kurrle et al (18). In the response to vaccinia virus, no CTL restricted to D k could ever be demonstrated.…”
Section: Involvement Of Helper Cells In Thesupporting
confidence: 71%
“…We have shown that preference of H-Y-specific CTL for H-2 k occurs also in B6 --~ B6 X CBA chimeras, i.e., that the radioresistant tissue of the chimeric hosts influences the preference of H-Y-specific CTL for certain H-2 alleles (14). Similar observations on allele preference of virus-specific CTL have been made by Zinkernagel et al (15,16), Doherty et al (17), and Kurrle et al (18). In the response to vaccinia virus, no CTL restricted to D k could ever be demonstrated.…”
Section: Involvement Of Helper Cells In Thesupporting
confidence: 71%
“…Our findings are similar to those reported for CTL responses against vaccinia and Sendai virus (12). It was suggested that the failure to generate CML responses against vaccinia and Sendai virus recognized in association with D k self products may be attributable to/r genes mapping to the H-2D region (12).…”
supporting
confidence: 79%
“…These observations can be accounted for by at least two models. It is possible that certain genes (lr genes) for CML that are distinct from the structural genes coding for self-recognition products map within the K and D regions (12). Alternatively, it is possible that the lack of or magnitude of a CTL response is primarily attributable to the antigenic properties of each particular K-and D-region-coded molecule.…”
mentioning
confidence: 99%
See 2 more Smart Citations